Multilateral rules on foreign direct investment - Phedon Nicolaides (Intereconomics, 1993)
During the last decade the world stock of foreign direct investment has more than doubled. Nevertheless, considerable impediments to FDI continue to exist. The following paper discusses these and offers an answer to the question as to whether multilateral rules on FDI are necessary to remove these barriers and what form these rules could take.
Keywords: 330; Foreign Direct Investment